Biodiversity and conservation planning of the amphibians and reptiles in the Western Mediterranean Basin - Carvalho, Sílvia Ricardo Benoliel de, 1978- (2010)
Tese de doutoramento, Biologia (Biodiversidade), Universidade de Lisboa, Faculdade de Ciências, 2010